Fat mass and obesity-associated protein regulates RNA methylation associated with depression-like behavior in mice - Shu Liu (Nature Portfolio, 2021)
Post-transcriptional modification of RNA can contribute to regulating behavior. Here, the authors show that modulating the expression of Fto results in epitranscriptomic changes in the mouse hippocampus associated with depression-like behavior.